Life-based narratives effects on student concept understanding and decision-making skills in Biology - Arcilla, Esperanza I. (Education Quarterly, 2013)
The study aimed at assessing the effect of students' life-based narratives in furthering concept understanding and decision-making skills among second year high school students of a public high school. The study made use of two instruments: the Concept Understanding Test (multiple choice test) and the Decision-making Skills Test (open ended questionnaire). Using analysis of covariance (ANCOVA) on the posttest scores of the experimental and control groups with the pretest scores as covariate, it was revealed that the use of students' life-based narratives as a teaching approach has a positive effect on the concept understanding of the students. However, the said approach has no significant effect on the students' decision-making skills. In terms of establishing the causal relationship between concept understanding and decision-making skills, linear regression showed that concept understanding can predict the decision making skills of students.